2013
DOI: 10.1038/ijo.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Addiction potential of phentermine prescribed during long-term treatment of obesity

Abstract: Phentermine abuse or psychological dependence (addiction) does not occur in patients treated with phentermine for obesity. Phentermine treatment does not induce phentermine drug craving, a hallmark sign of addiction. Amphetamine-like withdrawal does not occur upon abrupt treatment cessation even at doses much higher than commonly recommended and after treatment durations of up to 21 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 38 publications
0
31
0
5
Order By: Relevance
“…Evaluation of phentermine’s addictive potential revealed no abuse liability in overweight, obese and weight loss maintenance patients (Hendricks et al, 2014). Amphetamine-like withdrawal was absent upon abrupt treatment cessation at doses much higher than commonly recommended and after treatment durations of up to 21 years (Hendricks et al, 2014). …”
Section: Pharmacotherapies For Obesitymentioning
confidence: 99%
“…Evaluation of phentermine’s addictive potential revealed no abuse liability in overweight, obese and weight loss maintenance patients (Hendricks et al, 2014). Amphetamine-like withdrawal was absent upon abrupt treatment cessation at doses much higher than commonly recommended and after treatment durations of up to 21 years (Hendricks et al, 2014). …”
Section: Pharmacotherapies For Obesitymentioning
confidence: 99%
“…12 Neuropsychiatric related adverse events were also more common, including depression (7%, 33), anxiety (4%, 50), irritability (3%, 50), insomnia (10%, 20), and disturbances in attention (4%, 33). 12 Although phentermine-ER topiramate (15 and 92 mg/d, respectively) increases heart rate by about 2 beats/min, the FDA judged that the potential increase in cardiovascular risk was balanced by improvements in blood pressure and other cardiovascular risk factors.…”
Section: Phentermine-er Topiramatementioning
confidence: 99%
“…Phentermine was approved as an anti-obesity agent by the FDA in 1959 for shortterm management [40] and was approved again when combined with topiramate in 2012 [40] . A recent study for long-term use has shown that phentermine is not associated with addiction and drug-craving behaviour [41] . Phentermine is not associated with serious risk, although high blood pressure due to vasoconstriction and vasculopathies has been reported [42] .…”
Section: Anti-obesity Drugs and Monoaminesmentioning
confidence: 99%